Training and Fidelity Monitoring of Alcohol Treatment Interventions Integrated Into Routine Tuberculosis Care in Tomsk, Russia: the IMPACT Effectiveness Trial. (6th June 2013) - Connery, Hilary; Greenfield, Shelly; Livchits, Viktoriya; McGrady, Lana; Patrick, Nickolette; Lastimoso, Charmaine S.; Heney, Jessica H.; Nelson, Adrianne Katrina; Shields, Alan; Stepanova, Yekaterina P.; Petrova, Lidia Y.; Anastasov, Oleg V.; et al.
<x xml:space="preserve">Abstract</x> IMPACT (Integrated Management of Physician-Delivered Alcohol Care for Tuberculosis patients) is a randomized, controlled effectiveness trial based in Tomsk, Russia, that assesses the effect of oral naltrexone and brief behavioral counseling on tuberculosis outcomes and alcohol use in 200 patients. Tuberculosis physicians without addiction experience delivered interventions as part of routine care over a 6-month period, focusing on alcohol intake reduction to support successful tuberculosis treatment. We describe design, training, and fidelity monitoring using a Russian and American team of physicians, bilingual coders, and supervisors. Culturally appropriate adaptations, limitations, and implications for future trials are discussed. The clinical trial identification number is NCT00675961. Funding came from the National Institutes of Health and National Institute on Drug Abuse.